Malnutrition and quality of life among older persons in Kandy district, Sri Lanka: A mixed method study / Hewartne Dassanayakege Wimala Thushari Damayanthi - Hewartne, Dassanayakege Wimala Thushari Damayanthi (2018)
Malnutrition among older persons is a multi-dimensional problem. It predisposes the older persons to increased risk of hospitalisation, disability and mortality; and decreased quality of life (QoL). However, little is known about malnutrition and QoL among older persons in community settings in Sri Lanka. Therefore, this study aimed to investigate the malnutrition and QoL among community-dwelling older persons in Sri Lanka. A mixed methodology approach was used in two phases. A cross sectional design was done in the first phase. Seven divisional secretariats in Kandy district were selected using multi-stage sampling. The nutritional status was assessed using the Mini Nutritional Assessment- Short Form (MNA-SF). Quality of life was assessed using Euro 5D 3L index and visual analogue scale. Demographic data and factors associated with malnutrition were recorded using a standardised questionnaire. Physical activity was measured using International Physical Activity Questionnaire. Depression was assessed using Geriatric Depression Scale. Data analysis was done using Complex sample logistic regression. The second phase was a qualitative design. Fifteen focus group discussions were conducted among the purposefully selected malnourished older persons to explore the factors of malnutrition. Thematic analysis was executed in data analysis to identify the themes on factors related to malnutrition. The response rate of phase 1 was 76.85% (n=999). Majority of the respondents were females (71.9 %) with mean age 72.29 years (95% confidence interval: 70.59, 73.98). The prevalence of malnutrition, at risk of malnutrition and well-nourished were 12.5%, 52.4% and 35.1%. Alcohol consumption (aOR: 4.06, 95% CI: 1.17, 14.07), hypertension (aOR: 1.71, 95% CI: 1.02, 2.89) and age (aOR:1.06., 95% CI: 1.01, 1.11) had increased odds for malnutrition. For every additional number of person living with the older person, there iv was 9% reduced odds of being malnutrition (aOR: 0.91, 95% CI: 0.85, 0.97). The mean QoL score was 0.44 (95% CI: 0.42, 0.46). Age ( β -0.02, 95% CI: -0.02,-0.01) and higher physical activity (β: 0.10, 95% CI: 0.02, 0.19) showed significant association with QoL.The qualitative phase explored factors influencing malnutrition identified four main themes: factors affecting dietary patterns, factors affecting food choices, health status and psychological challenges. These themes appear to confirm the influencing factors identified from the quantitative data. The various psychological challenges reported serve to highlight not only the physical but also psychosocial factors that can influence nutrition status. The prevalence of malnutrition in Sri Lankan communitydwelling older persons is similar to international figures. Early identification of at risk of malnourished older persons is crucial. Our results are useful for the planning of intervention programs to improve the nutritional status and quality of life among older persons in the community settings.